Exploring Power and Identity in Liminal Spaces in Kapka Kassabova’s 'Border: A Journey to The Edge of Europe' (Proceedings of English Linguistics and Literature, 2022)
Travel writing has a long history dating back to early modern European colonial era in the 16th century. However, in the 21st century the role of travel writing is redefined and reconceptualized as the world becomes more globalized and connected. This paper attempts to investigate further the potential of travel writing to represent social, historical, and political issues. Using textual analysis, the research focuses on the discourses of power and identity as depicted in Kapka Kassabova’s Border: A Journey to The Edge of Europe (2017). The portrayal of border zones as liminal spaces is also discussed in this paper. The analysis shows that liminal spaces can be interpreted as the sites where power and identity are constantly challenged and negotiated. It reveals that liminal spaces are hardly neutral but contain ideological conflicts. It is expected that the result of the study will contribute a new perspective to the discussion of contemporary travel writing, especially in the post-pandemic era.